فقہ السیرۃ: ڈاکٹر محمدحمید اللہ کی اجتہادی فکر کا مطالعہ: Fiqh-Al-Sirah, A Study of Neologies Thought of Dr. Muhammad Hamidullah - Dr. Muhammad Abdullah (Seerat Studies, 2023)
Dr. Muhammad Hamidullah (1908-2002) was a great Islamic Scholar of the twentieth century. The scope of his Contribution was spread over the Holy Quran, Hadith, Biography of the Prophet Muhammad (PBUH) and International Relations. More or less in each of above fields he composed numerous articles and writings, which comprise on huge collections of Books in different dialects. Most of the research work of Dr. Hamidullah is about the life of Prophet Muhammad (PBUH). His famous books are مجموعة الوثائق السياسية للعهد النبوي والخلافة الراشدة The Muslim Conduct of State۔ Battlefields of the Prophet Muhammad, The Political life of Prophet Muhammad (PBUH), The First Written Constitution in the World The Prophet's Establishing a State and his Succession. He doesn't examine the Sirah in the conventional way in spite of the fact, he applies the lessons of Prophet (PBUH) in the contemporary age. Which is the one of a kind neologian nature of Hamidullah. In this Paper following aspects of his writings will be mentioned. His research in Geography and Seerah. Lessons from the journey of Migration, inferential lessons from Charter of Madina, ratiocinative teachings from the preaching of Prophet Muhammad (PBUH) and relations with Non-Muslims. Hopefully due to this research in Fiqh-Al-Sirah, new aspects of Research will be highlighted.